SEMA BINDING STRENGTH NO. 2/2023 REGARDING THE JUDGE'S DETERMINATION IN APPLICATIONS FOR REGISTRATION OF INTERFAITH MARRIAGES - Leonide, Cliff Ivan; Khoidin, M.; Zulaika, Emi; Poesoko, Herowati; Suci, Ivida Dewi Amrih (Awang Long Law Review, 2024)
The state guarantees freedom of religion, as well as forming a marriage. Registration of marriages, especially mixed marriages, is regulated in Article 57 of Law no. 16 of 2019 concerning Marriage. This mixed marriage is also related to interfaith marriage which is also a right for Indonesian citizens. The Supreme Court in this case made SEMA No. 2/2023 dated 17 July 2023 concerning Appointments for Judges in Adjudicating Cases on Applications for Registration of Marriages Between People of Different Religions and Beliefs, at point No. 2 explains that "The court did not grant the request for registration of marriages between people of different religions and beliefs." If this SEMA is analyzed it is in conflict with Article 35 letter (a) of Law no. 23 of 2006 in conjunction with Article 50 of Minister of Home Affairs Regulation no. 108/2019. Therefore, the author analyzes the binding strength of SEMA No. 2/2023 dated 17 July 2023 regarding the failure to grant the request for registration of interfaith marriages. Meanwhile, Minister of Home Affairs Regulation no. 108/2019 states that interfaith marriages must be proven, which automatically results in an application being made to the court. This is also related to Article 35 letter (a) of Law no. 23 of 2006 concerning Population Administration which regulates marriages determined by courts for people of different religions. Therefore, the author analyzes the above problem with the problem, namely the binding force of SEMA No. 2/2023 regarding the judge's decision in the application for registration of interfaith marriages. The method used is normative juridical research, with an analysis of the theory of authority and legal certainty. The approaches used are the conceptual approach, statutory approach and case approach. The conclusion to be reached in this writing has future perspective value and is in accordance with its axiology, namely the aim of law is justice.